Drought Monitoring and Assessment - Sharath L.,; Shivakumara N.,; Vinay Krishna H. V.,; Vinayak Venkatraman Hebbar,; Mr. Vivek Raj K, (Journal of Power Electronics and Devices, 2019)
The predictions of rainfall are not accurate, which might lead to floods or drought due to which risk occurs. Here we are going to discuss drought risk management in which Drought monitoring is an essential component. It is usually carried out using drought indicators. Remote sensing and hydrologic modeling techniques are used to generate a suite of drought monitoring indicators. Drought indicators such as standardized precipitation index, dryness indicators, and start of season analysis are produced using Satellite-based rainfall estimators. Vegetation condition is monitored using Normalized Difference Vegetation Index. Agro-hydrologic models are used to combine several satellite data products to produce multiple short- and long-term indicators of droughts. The availability of timely info and merchandise support the decision-making processes in drought-related hazard assessment, monitoring, and management with the FEWS internet.